Knockdown of circ_0003204 alleviates oxidative low-density lipoprotein-induced human umbilical vein endothelial cells injury: Circulating RNAs could explain atherosclerosis disease progression - Su Qiuxia (De Gruyter, 2021)
Atherosclerosis (AS) is a serious cardiovascular disease. Circular RNAs (circRNAs) play an important role in the progression of many diseases, including AS. However, the role of circ_0003204 in AS is not clear. Oxidized low-density lipoprotein (ox-LDL)-induced human umbilical vein endothelial cells (HUVECs) were used to construct an AS cell model in vitro. Cell viability was assessed using cell counting kit 8 (CCK8) assay. Flow cytometry and caspase-3 activity were used to measure cell apoptosis. The contents of inflammatory cytokines were measured using enzyme-linked immunosorbent assay (ELISA). Oxidative stress marker expression and cell injury marker activity were detected by their corresponding Assay Kits. Besides, the expression levels of circ_0003204, miR-330-5p, and toll-like receptor 4 (TLR4) were tested by real-time polymerase chain reaction (qPCR). The interaction between miR-330-5p and circ_0003204 or TLR4 was examined by dual-luciferase reporter assay and RNA pull-down assay. Western blot (WB) analysis was used to determine the levels of TLR4 protein and nuclear factor-kappa B (NF-κB) signaling pathway-related protein. Our data suggested that ox-LDL could suppress viability and promote apoptosis, inflammatory response, and oxidative stress in HUVECs. circ_0003204 was highly expressed in ox-LDL-induced HUVECs, and its silencing could inhibit ox-LDL-induced HUVECs injury. miR-330-5p could be sponged by circ_0003204, and its inhibitor could reverse the inhibition effect of silenced circ_0003204 on ox-LDL-induced HUVECs injury. Further, TLR4 could be targeted by miR-330-5p, and its overexpression could invert the suppression effect of miR-330-5p on ox-LDL-induced HUVECs injury. The activity of the NF-κB signaling pathway was regulated by the circ_0003204/miR-330-5p/TLR4 axis. Our results indicated that circ_0003204 silencing could alleviate ox-LDL-induced HUVECs injury, suggesting that circ_0003204 might be a novel target for AS treatment.